Tragdy versus irony - Kopeć, Anna (Hybris, 2016)
The article compares two approaches of subjectivity: ‘tragic subjectivity’ and ‘ironic’ one. Both of them include different anthropology. Tragic subjectivity is most fully expressed in commitment to values. Tragic protagonist is the one who by acting according to his commitment to values becomes self–conscious. However, subjectivity which emerges from tragic vision cannot exist in postmodern times, because of some reductions which postmodern philosophy has brought.Ironic subjectivity took the place of the tragic one. This subjectivity manifests in negation. Ironic protagonist understands freedom as being uncommitted, as an abstraction from the externality. This escape from reality brings to the subject the feeling of self–doubt.In the end of the article the author shows that ironic project is not a remedy for the problems which appear from postmodernity and suggests that new form of tragic vision (which again brings to the notion of ‘humanity’ special content) is possible.